Elaboration of artisanal caxiri beer with addition of camu-camu (Myrciaria dubia) - Gonçalves, Juliana Neves; Souza, Patrick Gomes de; Barreto, Eberson da Costa Mena; Lima, Jardel Silva de; Silva, Viviana Balieiro da (Brazilian Journal of Science, 2022)
In 2020, Brazil presented a growth of 14.4% in the number of breweries compared to 2021. This segment has been gaining ground with scientific studies that seek innovations in beers with more pronounced aromas and flavors. Based on this, the present study aims to develop and evaluate a craft beer of the Caxiri Beer style with the addition of camu-camu pulp. The camu-camu fruits were selected, pulped, blanched and frozen until use. The fruits, cassava starch and guarana syrup were evaluated for pH, acidity, soluble solids, density and ratio. The beer was prepared in a volume of 20L, in an aluminum pan, equipped with a false bottom and bagasse was washed. At the end of the process, the beers were evaluated for pH, density, color, bitterness, turbidity, BU/GU ratio, RBR, and subjected to sensory characterization analysis by Beer Sommeliers. The camu-camu pulp had an original density of 1.021 SG, moisture of 92.56% and pH of 2.77. The cassava starch presented a moisture content of 5.4% and a density of 1.035 SG. The guarana syrup had a moisture content of 88.57% and a density of 1.038 SG. Guarana syrup has a great influence on the color of the wort and, as a consequence, on the beer. The beer presented OG 1.050 SG, bitterness of 8.5 IBU, final apparent extract of 2.25 ºP, alcohol content of 5.2 % v/v. The BU/GU ratio with close and low results, shows a balanced and low intensity beer. The RBR below 0.5 shows a beer with low bitterness, easy to be consumed. Caxiri beer with camu-camu presented a copper color, with a fruity flavor, slightly acidic, with a cloudy appearance. Refreshing, slightly bitter and balanced. All the raw materials used in the present study showed excellent behavior on the beer and that the Caxiri Beer style can become the first style with important Amazonian characteristics in its formulation.